Characterization of particulate and gaseous pollutants emitted during operation of a desktop 3D printer. (February 2019) - Gu, Jianwei; Wensing, Michael; Uhde, Erik; Salthammer, Tunga
Abstract: The emission of ultrafine particles (UFP) and gaseous pollutants from 3D printing has been increasingly gaining attention in recent years due to potential health risks. The physical and chemical properties of the emitted particulate matter, however, remain unclear. In this study, we characterized these particles with a focus on their chemical composition and volatility, and measured the gaseous pollutants from desktop 3D printing in a standardized environmental test chamber. Eight types of filaments were tested, including ABS (acrylonitrile butadiene styrene), ASA (acrylonitrile styrene acrylate), HIPS (high impact polystyrene), PETG (polyethylene terephthalate glycol), and PCABS (polycarbonate & ABS). Particle size distribution (PSD), particle number concentration (PNC), particle chemical composition and particle volatility were measured. In addition, volatile and very volatile organic compounds (VOCs and VVOCs) emitted during 3D printing were analyzed. The specific emission rates (SERs) for particles in the size range of 5.6 to 560 nm ranged from 2.0 × 10 9 (GLASS, a PETG-based filament) to 1.7 × 10 11 (ASA) #/min. The particle SERs for ABS were (4.7 ± 1.1) × 10 10 #/min. The SERs for total volatile organic compounds (TVOC) varied from 0.2 μg/min (GLASS) to 40.5 μg/min (ULTRAT, an ABS-based filament). Particles started to evaporate extensively from 150 °C. At 300 °C, only 25% of the particle number remained with the size distribution mode peaked at 11 nm. The particles collected on the quartz filter were mainly composed of semi-volatile organic compounds (SVOCs) associated with the plasticizers, flame-retardants, antioxidants of the thermoplastics, and cyclosiloxanes which may be used as lubricants in the 3D printer. Graphical abstract: Unlabelled Image Highlights: We measured UFP and VOC emission from 3D printing with eight types of filament. UFP and VOC emission rates varied greatly, and were associated with filament types. 3D printing emitted particles mainly composed of semi-volatile organic compounds. Particles started to evaporate significantly from 150 °C.